Violence against women and its mental health consequences in Namibia - Nangolo, L. H. N (University of Limpopo, 2002)
Violence against women ts a manifestation of historically unequal power relations between men and women, which has led to the domination of women by men and to the prevention of the full advancement of women. It is an old phenomenon that was kept secret, and people pretended that the problem did not exist. It wasn't until the feminist activists openly addressed the issue of inequality that included women's lack of rights and low status within marriage and society as well as battering that the taboo topic was changed into a subject extensively investigated. Extensive research on the topic now exists. As is the case in many developing countries, research on violence against women in Namibia is relatively rare. Research regarding the mental health consequences of abuse is virtually non-existent. It is to this area of research that the present study addressed itself. This study aimed at describing and determining the mental health consequences of battering to which Namibian women are subjected. The study followed both qualitative and quantitative research approaches. Qualitative research used in-depth interviews based on a semi-structured questionnaire. The measures utilized was an Abuse Disability Questionnaire (ADQ). A demographic questionnaire identifying battered women variables was also utilized. A total of 60 battered women were surveyed and all 60 women completed the questionnaires. In quantitative methods, data were analysed in terms of descriptive statistics. In qualitative methods, closely related data were grouped together under specific titles to serve as categories. The results indicated that Namibian battered women endure physical, emotional, sexual and financial abuse. The results has shown that age, education, religion, employment status and marital status do not matter. Women are still being battered. The results also indicated that Namibian battered women are indeed subjected to various negative mental health consequences.
Thesis ((M.A. (Clinical Psychology)) --University of the North, 2002
Keywords: Violence; Women; Mental health; Women-Violence against -- Namibia; Abused women -- Namibia; Women-Mental health -- Namibia; Violence -- Namibia